Antibacterial, antibiofilm properties and mechanism of action of phosphanegold(I) thiolate complexes on Staphylococcus aureus strains - Alrawas, Anmar Ameer Mohammed Sadeq (2022)
With the widespread increase of bacterial resistance to available antibiotics and the lack of resources for the discovery of new classes of antibiotics, the multidrug-resistant S. aureus has become a global concern. The methicillin-resistant Staphylococcus aureus (MRSA) has been reported as a serious threat in health settings. There is now a strong demand for new antibacterial agents as only a few antibiotics can combat MRSA infections. The notable development of transition metals for medicinal purposes and advanced designs of metal complexes as antibacterial agents have been extended in the research area. These offer good choices as alternative antibacterial agents despite the fact that they have not been explored intensively. Recent in vitro studies have highlighted the potential use of gold-based compounds to inhibit the growth of important pathogens, such as MRSA without classifying the mode of action (MOA) or explaining the potential of the growth inhibition mechanism. This research study was aimed at evaluating and investigating the antibacterial activity, anti-biofilm activity, synergistic interaction, and classification of the mode of action of the novel 3F2 phosphanegold(I) thiolate compound. Preliminary screening using the disc diffusion method showed that the novel 3F2 gold compound possesses a noticeable antibacterial activity against MRSA strains with an average inhibition zone ranging between 8 mm to 12 mm. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the 3F2 gold compound against MRSA strains was in range of 4 μg/mL to 8 μg/mL. Moreover, the dose-dependent 3F2 gold compound exhibited bactericidal activity against MRSA during the first twelve hours. The interaction of the novel 3F2 compound in combination with ciprofloxacin showed a partially synergistic activity with FICI = 0.53 using the checkerboard method. Also, the Staphylococcus 3F2 gold compound showed an anti-biofilm activity, whereby cell viability was reduced by more than 50 percent. InCelligence technology and the CLSM microscopic results proved the inhibition/eradication of S. aureus biofilm formation with MIBC in the range of 3.125 μg/mL to 12.5 μg/mL. Furthermore, the predicted mode of action (MOA) of the 3F2 gold compound was classified based on a data analysis of the phenotypic microarray. The Pearson correlation and clustering analysis showed that the mode of action was similar to that of vancomycin in targeting the MRSA cell wall. However, the TEM and RT-PCR results supported the predicted mode of action. Finally, all the findings showed promising antibacterial activity by the new 3F2 gold compound, with a unique potential MOA against MRSA. Overall, the thesis results are beneficial for both the development of antibacterial agents and gaining an understanding of the mechanism of action to minimize the multi-drug resistance, and to develop new methods of identifying and classifying the mode of action of new antibacterial agents